The peaceful end-of-life theory in palliative care for the Muslim community and Indonesian context - Minanton, Minanton (Indonesian Nursing Journal, 2023)
Advances in health technology assist patients with life-threatening illnesses to survive longer, but a longer life does not mean to live better. Patients with life-threatening illnesses experience a variety of physical problems and psychosocial symptoms that affect their quality of life. Palliative care is a type of care that focuses on improving quality of life and alleviating the serious suffering of patients with chronic or terminal illnesses. The peaceful end of life theory developed by Ruland and Moore is one of the theories of care that can be applied. The concept is able to accommodate more holistic management of physical and psychological symptoms in terminal patients in end-of-life care. This theory consists of five main concepts: not being in pain, experience of comfort, experience of dignity respect, being in peace, and closeness to significant others. Applying this theory is not only to provide good care using modern tools but also to focus more on care that prioritizes patient comfort and maximizes family involvement in patient care. So, at the end of life, patients can enhance the quality of life and face death with a sense of peace. A paradigm for peaceful end-of-life care for Muslim communities in Indonesia incorporates Islamic beliefs and the local environment.